The Effect of Family Caregiver Empowerment Model Intervention on Fear of Hypoglycemia in People with Type-2 Diabetes Mellitus - Rondhianto, Rondhianto; Kushariyadi, Kushariyadi; Rahmatullah, M. Nauval (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: The family plays a vital role in T2DM self-management, but many families need to understand their role and function as caregivers. This lack of understanding can increase the burden of disease management, contributing to the emergence of psychological problems in people with T2DM, such as fear of hypoglycemia, which in turn worsens blood glucose control. The Family Caregiver Empowerment Model (FCEM) intervention is one model that can be used to empower families as caregivers in T2DM self-management.Purpose: This study aimed to analyze the effect of the FCEM intervention on the fear of hypoglycemia in people with T2DM. Methods: The study design was quasi-experimental with a randomized control pretest-posttest design. The sample size consisted of 85 respondents (a pair of family caregivers and people with T2DM), who were randomly divided into two groups: the treatment group (41 respondents) and the control group (44 respondents). The FCEM intervention was conducted once per week for ten weeks for family caregivers, and fear of hypoglycemia was measured using the Indonesian version of the Fear of Hypoglycemia Scale questionnaire. The data were analyzed using the Wilcoxon signed rank test and independent t-test.Results: The results showed significant differences in fear of hypoglycemia between the pre-test and post-test in the treatment group (p=0.001) and the control group (p=0.001). However, there was a significant difference in the decrease of fear of hypoglycemia between the treatment and control groups (t=-7.087; p=0.001). This finding suggests that FCEM intervention can significantly reduce the fear of hypoglycemia in people with T2DM.Conclusions: The FCEM intervention can reduce the fear of hypoglycemia in people with T2DM by increasing the family caregiver’s ability and support in managing T2DM. Nurses can use the FCEM intervention in T2DM management to improve diabetes management outcomes.